Dynamics of extreme and non-extreme poverty: analysis for Peru (2003-2006) - Chumpitaz Torres, Annie (2008)
In Peru, there are papers that study the dynamics of poverty; nevertheless, these documents do not make differences between levels of severity: extreme poverty and non-extreme poverty. In this sense, the main objective of this research is to identify the factors that make the households slip into and out of the extreme and non-extreme poverty in Peru (2003-2006).This paper finds out that there are different factors that make extreme and non-extreme poor households arrive to non-poverty. In this sense, the elements that only contribute to extreme poor households to reach the non-poverty are: housing conditions, literacy programs, shocks protection and politics of participative public management. Moreover, the tools that only facilitate the non-extreme poor households to slip out of poverty are non-university high education, credit access and productive assets. Finally, in order to make both groups (extreme and non-extreme poor households) become non poor, it is necessary a set of actions: to improve the quality of education; to expand the coverage and quality of medical services and familiar planning; to emphasize the productive use of remittances; to make politics with a community approach; and to develop insurance for poor people so as to mitigate the effect of shocks.On identifying the factors that generate the changes of welfare states, this research provides lights to tune the focalization and effectiveness of social policies, so that these are more in line with the heterogeneity and multidimensionality of poverty.